Changing mechanism of global water scarcity events: Impacts of socioeconomic changes and inter-annual hydro-climatic variability. (May 2015) - Veldkamp, Ted I.E.; Wada, Yoshihide; de Moel, Hans; Kummu, Matti; Eisner, Stephanie; Aerts, Jeroen C.J.H.; Ward, Philip J.
Highlights: We execute a scenario analysis to assess the mechanism of global water scarcity. We quantify over-/underestimates in water scarcity if studied under fixed conditions. Hydro-climatic and socioeconomic conditions interact, influencing scarcity events. Hydro-climatic variability accounts for >79% of the yearly change in water scarcity. Socioeconomic changes become the most important driving force only after 6–10 years. Abstract: Changes in available fresh water resources, together with changes in water use, force our society to adapt continuously to water scarcity conditions. Although several studies assess the role of long-term climate change and socioeconomic developments on global water scarcity, the impact of inter-annual climate variability is less understood and often neglected. This paper presents a global scale water scarcity assessment that accounts for both temporal changes in socioeconomic conditions and hydro-climatic variability over the period 1960–2000. We thereby visualized for the first time possible over- and underestimations that may have been made in previous water scarcity assessments due to the use long-term means in their analyses. Subsequently, we quantified the relative contribution of hydro-climatic variability and socioeconomic developments on changing water scarcity conditions. We found that hydro-climatic variability and socioeconomic changes interact and that they can strengthen or attenuate each other, both regionally and at the global scale. In general, hydro-climatic variability can be held responsible for the largest share (>79%) of the yearly changes in global water scarcity, whilst only after six to ten years, socioeconomic developments become the largest driver of change. Moreover, our results showed that the growth in the relative contribution of socioeconomic developments to changing water scarcity conditions stabilizes towards 2000 and that the impacts of hydro-climatic variability remain significantly important. The findings presented in this paper could be of use for water managers and policy makers coping with water scarcity issues since correct information both on the current situation and regarding the relative contribution of different mechanisms shaping future conditions is key to successful adaptation and risk reduction.